2018
DOI: 10.16948/zktipb.331345
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Factors Affecting The Social And Academic Adjustment of International Students Studying At a Public University

Abstract: Bu çalışma bir kamu üniversitesinde öğrenim gören yabancı uyruklu öğrencilerin sosyal ve akademik uyumları ve etkileyen faktörlerin belirlenmesi amacıyla yürütüldü.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 4 publications
(3 reference statements)
2
2
0
Order By: Relevance
“…Preliminary results suggest that international exhibit a substantial propensity for adaptation. Some studies, including those by Arslan and Polat (2023), Aydın-Kartal et al (2018), Karakuş and Akay (2020), Karakuş and Karakuş (2022), have reported results consistent with this study. The results also indicate that international students generally do not encounter significant issues with university rules and guidelines.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Preliminary results suggest that international exhibit a substantial propensity for adaptation. Some studies, including those by Arslan and Polat (2023), Aydın-Kartal et al (2018), Karakuş and Akay (2020), Karakuş and Karakuş (2022), have reported results consistent with this study. The results also indicate that international students generally do not encounter significant issues with university rules and guidelines.…”
Section: Discussionsupporting
confidence: 90%
“…The results of the present investigation indicate that international students pursuing higher education in Turkey demonstrate comparatively elevated levels of academic adjustment and that these levels are not significantly affected by diverse study variables. This aligns with prior research exploring international students' academic adaptation in different contexts (e.g., Aydın, 2020;Aydın-Kartal et al, 2018;Dziwornu et al, 2016;Ercan, 2019;Karakuş & Akay, 2020;Reis & Gulsecen, 2014;Tekin & Orhan, 2023). However, it is worth noting that some challenges in academic experiences were identified, indicating exceptions to the overall positive trend.…”
Section: Recommendationssupporting
confidence: 88%
See 1 more Smart Citation
“…The high level of social adaptation of the participants may be an indication that the foreign students get efficiency from the orientation trainings or guidance and counselling services provided in the university. Because universities play a key role in facilitating the adaptation of foreign students to the new social environment they are in (Aydın-Kartal et al, 2018). Foreign students who participated in the study of Kıroğlu et al (2010) stated that they preferred to make friends with people from their own countries more, then they made friends with Turkish students, that they did not feel excluded, that the Turkish people did not act prejudiced against them, and that they did not experience adaptation problems due to their similarity of the traditions and customs in Turkey and their own culture.…”
Section: Discussionmentioning
confidence: 99%